Cat among the pigeons : a Hercule Poirot mystery - Christie, Agatha, 1890-1976. (New York : Berkley Books, 2000)
Detective Hercule Poirot sets out to catch a killer when murder becomes part of the curriculum at the Meadowbank school for privileged young ladies.
Young Adult
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Private investigators -- Fiction